Microwave freeze‐drying of button mushroom (Agaricus bisporus) based on non‐volatile taste components by controlling microwave power density. (10th November 2021) - Duan, Xu; Miao, Junwei; Huang, Luelue; Li, Bin
Summary: The present study was carried out to establish a dynamic microwave loading strategy for efficient production of high‐quality microwave freeze‐dried button mushroom based on non‐volatile taste components. The change behaviour of non‐volatile taste components of mushroom, including free amino acids and 5′‐nucleotides, was evaluated during microwave freeze‐drying with fixed microwave power. Then, the dynamic microwave loading strategy was established according to the change behaviour of the non‐volatile taste components. Drying and quality characteristics of mushroom were evaluated in terms of drying time, whiteness index, shrinkage ratio, rehydration ratio and vitamin C content. Results showed that high microwave power led to higher contents of free amino acids and 5′‐nucleotides at the initial stage of drying, but more degradation of these non‐volatile taste components was observed during the last period of drying. Moreover, it takes longer for 5′‐nucleotides to reach the highest content than total free amino acids. According to the evolution of non‐volatile taste components, a step‐down dynamic microwave power loading program (0–1.5 h: 4 W g −1 ; 1.5–4.5 h: 3 W g −1 and 4.5–10.5 h: 2 W g −1 ) was established to reduce the drying time, keeping a relatively high product quality. Abstract : Based on the dynamic monitoring of the change behavior of non‐volatile flavor substances during microwave freeze‐drying of mushrooms, a variable microwave power loading strategy was proposed. The results show that this microwave loading strategy can significantly improve the quality of microwave freeze‐dried mushroom products.